Edukasi Kesehatan Mental di Masa Pandemi Covid-19 melalui Sharing Session Bertemakan “Quarter-Life Crisis” bagi Remaja Usia 20 Tahunan - Sukma Dwi Lestari; Syifaul Fuada (Jurnal Pengabdian Pada Masyarakat, 2021)
MENTAL HEALTH EDUCATION IN THE COVID-19 PANDEMIC PERIOD THROUGH SHARING SESSION PROGRAM “QUARTER-LIFE CRISIS” FOR 20 YEARS OLD ADOLESCENT. The Covid-19 pandemic is threatening physical health and affects a person’s psychological health (mental health). The pandemic period is one of the causes of mental crises in society, especially among adolescents, such as parents’ economic pressures that are affected by the Covid-19, excessive anxiety due to negative news related to Covid-19 from various social media, fear and worries about the future due to Covid-19 crisis, difficulty sleeping due to long duration of self-quarantine, emotional feelings that they cannot control, and many more problems. The mentality faced by teenagers during this Covid-19 pandemic is usually faced by late adolescents who will enter the phase towards early adulthood. The mental crisis of adolescents is known as a Quarter-Life Crisis. Therefore, mental health education or counseling is needed to be carried out for adolescents. In this paper, we report a sharing session program with the topic of “The impact of Covid-19 Pandemic on mental health and Quarter-Life Crisis” which is held on the Zoom meeting platform (December 21, 2020). This sharing session invited the professional/certified hypnotherapists and was attended by an audience of teenagers aged 20-23 who came from various regions in West Java. The results showed that most participants responded positively because the program was helpful, the topic was interesting, and the contents (sharing session materiasl) were according to what they needed.